2009
DOI: 10.1074/jbc.m109.032631
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible Factor Prolyl-4-hydroxylase PHD2 Protein Abundance Depends on Integral Membrane Anchoring of FKBP38

Abstract: Prolyl-4-hydroxylase domain (PHD) proteins are 2-oxoglutarate and dioxygen-dependent enzymes that mediate the rapid destruction of hypoxia-inducible factor ␣ subunits. Whereas PHD1 and PHD3 proteolysis has been shown to be regulated by Siah2 ubiquitin E3 ligase-mediated polyubiquitylation and proteasomal destruction, protein regulation of the main oxygen sensor responsible for hypoxia-inducible factor ␣ regulation, PHD2, remained unknown. We recently reported that the FK506-binding protein (FKBP) 38 specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
47
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 77 publications
(116 reference statements)
10
47
1
Order By: Relevance
“…The rapid recovery by 48 h under hypoxic conditions and the unchanged level with DFO treatment in this study, suggested that FKBP38 is not a HIF target, as previously reported (37). These results indicated that the early and immediate compensatory bio-responses of HAC2 cells against sudden and severe hypoxic changes were almost the same as those described in previous reports (33,36). A decreased level of HSP90 and slight but detectable increased level of HSP70 were additionally found (Fig.…”
Section: Genesupporting
confidence: 89%
See 1 more Smart Citation
“…The rapid recovery by 48 h under hypoxic conditions and the unchanged level with DFO treatment in this study, suggested that FKBP38 is not a HIF target, as previously reported (37). These results indicated that the early and immediate compensatory bio-responses of HAC2 cells against sudden and severe hypoxic changes were almost the same as those described in previous reports (33,36). A decreased level of HSP90 and slight but detectable increased level of HSP70 were additionally found (Fig.…”
Section: Genesupporting
confidence: 89%
“…Our present study also demonstrated that a VHL mutation did not appear in OCCC, different from renal clear cell carcinoma. In contrast, in the initial 24 h after hypoxic culture, the occurrence was noted of continuous 48-h overexpression and stabilization of PHD2, which is a HIF1 downstream gene and the main HIF1α regulator via hydroxylation of ODDD (33,34), and also of transient downregulation of FKBP38, a key regulator in the stabilization and function of PHD2 by binding, followed by proteasomal degradation (35)(36)(37) (Fig. 2C).…”
Section: Genementioning
confidence: 95%
“…These findings suggest that, assuming VHL exhibits complete functionality, HIF1 is able to induce PHD2-expression in a VHL-dependent manner in 3D culture under hypoxic conditions. As PHD2 is the main member of the PHD enzyme family that is involved in oxygen-sensing prolyl hydroxylation of the oxygen-dependent degradation domain in the HIF1 molecule (54,55), elevation and activation of PHD2 may have the compensatory effect of maintaining the HIF1 molecule as a mechanism leading to the hypoxic condition. In spite of equal levels of expression of mRNA between 2D and RFB cultured cells, there was a difference in the levels of PHD2 protein.…”
Section: Expression Of Hypoxia Inducible Factor 1 and Transcriptionalmentioning
confidence: 99%
“…In addition, FKBP38 appears to regulate protein degradation by anchoring the 26 S proteasome to organellar membranes (17). It thereby affects the stability of both Bcl-2 and the prolyl 4-hydroxylase domain-containing enzyme PHD2, the latter of which regulates the hypoxia-inducible transcription factor HIF1␣ (18). Although FKBP38 has been found to be expressed in all mammalian tissues examined, it is especially abundant in the central nervous system, both in neurons and in glial cells (19).…”
mentioning
confidence: 99%